Quantitating subcellular metabolism with multi-isotope imaging mass spectrometry - Steinhauser, Matthew L. (2012)
Mass spectrometry with stable isotope labels has been seminal in discovering the dynamic state of living matter(1,2) but is limited to bulk tissues or cells. We developed multi-isotope imaging mass spectrometry (MIMS) that allowed us to view and measure stable isotope incorporation with sub-micron resolution(3,4). Here we apply MIMS to diverse organisms, including Drosophila, mice, and humans. We test the “immortal strand hypothesis,” which predicts that during asymmetric stem cell division chromosomes containing older template DNA are segregated to the daughter destined to remain a stem cell, thus insuring lifetime genetic stability. After labeling mice with (15)N-thymidine from gestation through post-natal week 8, we find no (15)N label retention by dividing small intestinal crypt cells after 4wk chase. In adult mice administered (15)N-thymidine pulse-chase, we find that proliferating crypt cells dilute label consistent with random strand segregation. We demonstrate the broad utility of MIMS with proof-of-principle studies of lipid turnover in Drosophila and translation to the human hematopoietic system. These studies show that MIMS provides high-resolution quantitation of stable isotope labels that cannot be obtained using other techniques and that is broadly applicable to biological and medical research.